NEXUS BETWEEN FIRMS-SPECIFIC CHARACTERISTICS AND CASH HOLDING OF LISTED MANUFACTURING FIRMS IN NIGERIA - Shehu Aliyu; Ibrahim Shehu Nakazalle; Ibrahim Yusuf (Gusau Journal of Accounting and Finance, 2020)
This paper aims at shedding light on the empirical relationship between cash holding and firm characteristics. The population of the consist of 51 manufacturing firms listed on the Nigeria Stock Exchange, while the adjusted population of 35 firms was arrived based on availability of data. Correlational research design was adopted. The study was anchored on pecking order theory. Multiple regression was employed to analyse data extracted from annual report of selected manufacturing firms in Nigeria from the period of 2012 to 2019. The result of the findings shows that profitability and networking capital have positive and significant relationship on corporate cash holding. However, negative and significant relationship was found between leverage and corporate cash holding. In line with the findings, the study therefore recommends that managers of Nigerian manufacturing firms should develop a good strategy for earning high returns from their assets since this has positive significant effect on cash holdings. They should avoid holding excessive cash reserves as this might attract scrutiny from the capital markets. There should be an optimal trade-off approach to cash holdings, and also there should be a hierarchy explanation for holding excess cash.